Haematophagous arthropod saliva and host defense system: a tale of tear and blood - Andrade Bruno B.; Teixeira Clarissa R.; Barral Aldina; Barral-Netto Manoel (Anais da Academia Brasileira de Ciências, 2005)
The saliva from blood-feeding arthropod vectors is enriched with molecules that display diverse functions that mediate a successful blood meal. They function not only as weapons against host's haemostatic, inflammatory and immune responses but also as important tools to pathogen establishment. Parasites, virus and bacteria taking advantage of vectors' armament have adapted to facilitate their entry in the host. Today, many salivary molecules have been identified and characterized as new targets to the development of future vaccines. Here we focus on current information on vector's saliva and the molecules responsible to modify host's hemostasis and immune response, also regarding their role in disease transmission.